Faktor-faktor yang Mempengaruhi Sikap Konsumen dan Minat Pembelian Produk Handbag Merek Tiruan (Studi pada Konsumen Wanita di Kota Malang) - Aisyah, Ismi Nur; Setiawan, Margono; Sunaryo (Jurnal Aplikasi Manajemen, 2014)
The recent phenomena shows that the rising of Indonesian society consumerism is marked by numerous shopping malls and behavior of consumers in Indonesia who adore fashion products overseas rather than local products. This study aims to identify and analyze the effect of status consumption, value consciousness, price-quality inference, social influenceon purchasing counterfeit brand of handbag towards consumer attitudes on counterfeit products. This study used quantitative methods by conducting explanative research. The population in this study was all female consumers in Malang and the samples were obtained 120 female consumers. The data analysis methods used path analysis. The results show that attitude may mediate the effect of consumption status, value consciousness, price-quality inference, and social influence toward purchase intention of counterfeit brand of handbag products. The attitude towards counterfeit products affect purchase intention.